PENETAPAN PENGADILAN NEGERI SYARAT PENCATATAN PERKAWINAN BEDA AGAMA ANALISA YURIDIS PUTUSAN NOMOR : 87/PDT.P/2020/PN MKS. - Heriyanto; Mustofa (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
Based on the applicable provisions, interfaith marriages for each party involve a person's creed. This means that there are binding rules for every believer regarding the terms and procedures for the implementation of marriage by the laws of their respective religions. But on the other hand there is a legal obligation for the State to record the legal events of marriages carried out by citizens. This research is a juridical study in terms of marriage law and population administration law, on a case that was decided by a judge on an interfaith marriage that received court legitimacy on behalf of the State. In this study, using a normative juridical legal research method with a statute approach, namely by analyzing the issues or problems in this study, with the test stone of the applicable laws and regulations. So that the results of this study become an alternative reference for the legal events of interfaith marriages. Keywords: , ,